1983
DOI: 10.1128/aac.23.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and DNA-binding properties of substituted triostin antibiotics

Abstract: Novel derivatives of the triostin group of antibiotics were prepared by supplementing cultures of the producing organism Streptomyces triostinicus with a variety of aromatic carboxylic acids. Five new antibiotics, each having both the natural quinoxaline chromophores replaced by a substituted ring system, were purified to homogeneity and characterized by high-pressure liquid chromatography and nuclear magnetic resonance. Their antibacterial activities and DNAbinding properties were investigated. Addition of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Our method provides comparable results for the force dependence of the association constant to the results presented for ethidium (11). The derived zero force binding constant of K 0 ¼ (5.8 5 0.3) Â 10 5 M À1 compares favorably with a previously published value of K A (at F ¼ 0) z 10 6 M À1 , which was determined by a solvent partition method (8,9).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our method provides comparable results for the force dependence of the association constant to the results presented for ethidium (11). The derived zero force binding constant of K 0 ¼ (5.8 5 0.3) Â 10 5 M À1 compares favorably with a previously published value of K A (at F ¼ 0) z 10 6 M À1 , which was determined by a solvent partition method (8,9).…”
Section: Discussionsupporting
confidence: 74%
“…As a member of the quinoxaline family of antibiotics, Triostin A consists of a cyclic disulfide bridged backbone with two covalently linked quinoxalines that are well oriented for bisintercalation in dsDNA ( Fig. 1 a) (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Early feeding studies in S. triostinicus and S. echinatus using several structural analogs of QXC revealed that QXC acted as a free intermediate during triostin A and echinomycin biosynthesis 48, 58–61. In line with this observation, Keller and coworkers isolated and characterized the enzyme that activates QXC to QXC‐AMP in S. triostinicus and S. echinatus 62.…”
Section: Bisintercalators Biosynthesismentioning
confidence: 93%
“…Several synthetic and naturally occurring compounds containing the quinoxaline ring system were reported to exhibit a broad spectrum of biological activities including antitumor [5], anti-HIV [6], antimicrobial [7], antiprotozoal [8], antifungal [9], antibiotic [10,11], and human cyclophilin A inhibitor [12] properties. On the other hand, synthetic second generation fluoroquinolones (e. g. ciprofloxacin) [13] have recently emerged as potent antiinfectious drugs [13,14].…”
Section: Introductionmentioning
confidence: 99%